2013
DOI: 10.1007/s00497-013-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and cellular analysis of cross-incompatibility in Zea mays

Abstract: Three genetic systems conferring cross-incompatibility have been described in Zea mays: Teosinte crossing barrier1-strong (Tcb1-s) found in teosinte, and Gametophyte factor1-strong (Ga1-s) and Ga2-s found in maize and teosinte. The reproductive barrier between maize and some weedy teosintes is controlled by the Tcb1-s locus. Multi-generation inheritance experiments on two independent Tcb1-s lineages show that the Tcb1-s barrier is unstable in some maize lines. Reciprocal crosses between Tcb1-s tester plants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…Lu et al . observed that in silk carrying the Tcb , pollen tubes had clustered callose plugs and their growth was slower in comparison to pollen tubes of compatible crosses 37 . Such crossing incompatibility may also exist between commercial maize and Spanish teosinte.…”
Section: Discussionmentioning
confidence: 98%
“…Lu et al . observed that in silk carrying the Tcb , pollen tubes had clustered callose plugs and their growth was slower in comparison to pollen tubes of compatible crosses 37 . Such crossing incompatibility may also exist between commercial maize and Spanish teosinte.…”
Section: Discussionmentioning
confidence: 98%
“…Collections of teosinte of both mexicana and parviglumis subspecies from the central Mexican plateau carry Tcb1-s ( 6 ). Tcb1-s confers to females the ability to block fertilization by maize ( tcb1 type) pollen by restricting pollen tube growth ( 7 ). In the reciprocal cross, teosinte pollen is able to fertilize maize, although poorly when in competition with maize pollen ( 3 ).…”
Section: Main Textmentioning
confidence: 99%
“…The male and female functions of Tcb1-s are tightly linked but separable by recombination ( 7 ). Thus, there are four functional classes at this locus (Table S1 for gene content and origin): Tcb1-s has both functional male and female genes, Tcb1-m has only the functional male gene ( 6, 7 ), Tcb1-f has only the functional female gene, and the tcb1 haplotype found in almost all maize lines has neither of the two functional genes. In teosinte, Tcb1-f activity in the silks prevents fertilization by maize (tcb1) pollen, while Tcb1-m activity in pollen enables fertilization of Tcb1-f females ( 7 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of incompatibility is seen in Solanum 12, 13 , as well as in some Brassica species 14 . It is possible that the action of both the male and female may be conferred through the actions of a protein encoded by a single gene, or the male and female functions of a crossing barrier may be provided by separate genes in tight genetic linkage, as has been shown for tcb1 15 .…”
Section: Introductionmentioning
confidence: 99%